IMPLEMENTATION OF STUDENT CHARACTER BUILDING THROUGH THE 5S PROGRAM (SMILE, GREET, SALUTE, POLITENESS, COURTESY) AT SDIT EL-HAQ SIDOARJO - Eka Putri, Rahma; Ghozali, Solchan (PT. Antis International Publisher, 2025)
Objective: This study aimed to evaluate the integration of student character building through the 5S program (Smile, Greet, Salute, Politeness, Courtesy) at SDIT El-Haq Sidoarjo by assessing the implementation of general character education, teachers’ comprehension, and collaborative efforts of school principals and educators. Method: Employing a descriptive qualitative case study approach, data were collected through observations, interviews, and documentation, with analysis conducted via data reduction, presentation, and inference, and validity ensured through source and data triangulation. Results: Findings indicate that the 5S program is effectively embedded in daily school routines and curricular activities, with teachers exemplifying positive behavior and principals coordinating efforts that result in enhanced student discipline and social courtesy. Novelty: This investigation offers novel insights into the replicability of the 5S program as a holistic model for character formation, presenting a viable strategy to counteract the adverse influences of modern development while fostering a nurturing educational environment.